Implementasi Pembentukan Sistem Interdiksi Terpadu dalam Instruksi Presiden Republik Indonesia Nomor 2 Tahun 2020 pada Badan Narkotika Nasional - Lidyah Ayu Suhito Wardhani; Palupi Lindiasari Samputra; Margaretha Hanita (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
This paper aims to describe the Integrated Interdiction System's implementation in the National Narcotics Board to eradicate narcotics smuggling and illegal trafficking. Integrated Interdiction System is one of the actions included in government regulation called Instruksi Presiden Republik Indonesia Nomor 2 Tahun 2020 about national action plan to prevent and eradicate narcotics abuse and illegal trafficking (P4GN) 2020-2024. The theory used is the public policy analysis theory from William N. Dunn. At the phase of policy monitoring, used the social auditing approach. This paper used qualitative descriptive methods—primary data collected from interviews with the Integrated Interdiction System's implementor in National Narcotics Board. The secondary data collected from the literature study. This study's findings are the implementation of the Integrated Interdiction System fulfills three of four policy monitoring functions. Furthermore, concerned with the social auditing approach, Integrated Interdiction System fulfills the policy process of relations among input, process, output, and outcome.